1999
DOI: 10.1042/bj3380745
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal trefoil factor binds to intestinal epithelial cells and induces nitric oxide production: priming and enhancing effects of mucin

Abstract: Intestinal trefoil factor (ITF or TFF3), NO and epitheliumassociated mucin have important roles in sustaining mucosal integrity in the gastrointestinal tract. In the present study we examined ITF-binding molecules on IEC-18 cells (an intestinal epithelial cell line) with the use of flow cytometry and localized these molecules on the cell surface by confocal microscopy. Furthermore, we studied the interaction of mucin and ITF and their co-operative effect on NO production by the epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…At fi rst glance, TFFs appear to exhibit opposite effects on iNOS-derived NO production. TFF3 stimulates NO production through iNOS in the non-transformed rodent intestinal epithelial cell line, IEC-18 [74]. On the other hand, TFF2 is able to inhibit LPS-induced (but not basal) NO production in a monocyte cell line [75].…”
Section: Tffs and Modulation Of Immune Responsementioning
confidence: 95%
“…At fi rst glance, TFFs appear to exhibit opposite effects on iNOS-derived NO production. TFF3 stimulates NO production through iNOS in the non-transformed rodent intestinal epithelial cell line, IEC-18 [74]. On the other hand, TFF2 is able to inhibit LPS-induced (but not basal) NO production in a monocyte cell line [75].…”
Section: Tffs and Modulation Of Immune Responsementioning
confidence: 95%
“…This suggested that the decreased colonic contents of nitrated protein and the therapeutic effect of TFF2 in the DNBS model were directly related to a TFF2-mediated decrease in expression of iNOS [81,175]. TFF3, on the other hand, has been reported to increase production of NO via increased expression of iNOS, an effect which is enhanced by mucin [199]. Since NO has multiple functions including cytoprotection and anti-inflammatory effects, these in this respect apparently contrasting properties for TFF2 and TFF3 may not be conflicting [200].…”
Section: Immune Modulationmentioning
confidence: 97%
“…Thus, the combination of TFFs and mucins has been demonstrated to protect cell monolayers against injurious agents, to decrease proton permeation through mucus and to increase mucus viscosity [205 -207]. However, TFF-mucin interactions have also been shown to promote cellular effects like cell migration and NO production [179,199]. Due to variations in their structure, including the shape and numbers of putative mucin binding pockets [37] and free cysteines, it seems likely that each TFF may interact differently with the mucins.…”
Section: Mucin Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Fluorescence-activated cell sorting (FACS) analysis of non-enzymatically detached cells incubated at 4 °C indicated that fl uorescein isothiocyanate (FITC)-or phycoerythin-conjugated mouse anti-biotin antibody bound to the outer surface of these cells in a specifi c manner [19], and that the binding was increased by preincubating in mucin (5 mg/ml for 90 min), a situation that resulted in augmented nitric oxide production upon stimulation with rTFF2 (2.5 µM, 18 h). These data were interpreted as showing that the interaction of rTFF3 with IEC-18 cells was upregulated by mucin.…”
Section: Bt-rtff3 Binding To Iec18 Cells Augmented By Mucinmentioning
confidence: 99%